Composite photocatalyst and preparation method thereof
Patent Information
- Application Number
- CN202310800812.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing photocatalysts are inefficient in reducing CO2 to CH4, especially in visible light, and traditional synthesis methods are highly energy-consuming and complex in operation.
Cs2AgBiBr6 was grown in situ on g-C3N4 nanosheets by anti-solvent method to form CABB@g-C3N4 composite photocatalyst, which improved the photoresponse ability and electron/hole pair separation efficiency.
The catalytic efficiency of CO2 reduction is significantly improved, providing efficient photocatalytic carbon reduction materials, simplifying the synthesis steps and reducing energy consumption.
Smart Images

Figure CN119236978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalyst materials, and in particular to a composite photocatalyst and a preparation method thereof. Background Art
[0002] With the rapid economic development and the continuous deterioration of the ecological environment, climate change and environmental pollution issues have attracted more and more attention. In order to cope with the above problems, photocatalytic technology has emerged and has made great progress. Photocatalytic technology has attracted much attention in recent years due to its advantages such as high efficiency, cleanliness, and mild reaction conditions, and has been widely used in the fields of hydrogen production, carbon dioxide reduction, and pollutant degradation. It is quite challenging to directly convert hydrocarbons into high-value-added chemicals, which is usually costly, cumbersome to operate, and accompanied by a large number of side reactions. In an efficient photocatalytic system for converting CO2 into CH4, semiconductor catalysts should have a relatively negative conduction band position and a wider range of sunlight capture. However, existing photocatalysts generally have low catalytic efficiency, and it is difficult to achieve satisfactory results in actual production. Therefore, it is of great significance to develop and explore new photocatalysts.
[0003] g-C3N4 is a graphite-like semiconductor with good thermal and chemical stability, environmental friendliness, and no secondary pollution. Compared with traditional TiO2 photocatalysts, g-C3N4 has a wider absorption spectrum range and can play a photocatalytic role under ordinary visible light without ultraviolet light. It is a good catalyst and catalyst carrier, but its catalytic efficiency is low.
[0004] Halide perovskites have been widely used in solar cells, UV detectors, sensors, photocatalysis and other optoelectronic fields due to their adjustable band gap width, high light utilization efficiency, and low exciton binding energy. Compared with traditional lead-containing perovskites, lead-free bimetallic perovskite Cs2AgBiBr6 nanocrystals show high stability and can maintain their original crystal form even in aqueous catalytic systems, which is undoubtedly beneficial to actual production activities. However, the reducing property of Cs2AgBiBr6 is not enough to reduce CO2 to CH4. Even if a small amount of CH4 is generated, the efficiency is extremely low. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem of low efficiency of photocatalysts in reducing CO2 to CH4 in the prior art, and to provide a composite photocatalyst and a preparation method thereof, wherein the composite photocatalyst can efficiently reduce CO2 under visible light.
[0006] In order to achieve the above-mentioned object, the present invention provides a method for preparing a composite photocatalyst on one hand, the method comprising: using an anti-solvent method to in-situ grow Cs2AgBiBr6 on g-C3N4.
[0007] Preferably, the method comprises the following steps:
[0008] (1) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution;
[0009] (2) mixing g-C3N4 with N,N-dimethylformamide, and then mixing with the precursor solution to obtain a mixed solution;
[0010] (3) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst;
[0011] Wherein, in step (1), the mixed solvent contains N,N-dimethylformamide and dimethyl sulfoxide.
[0012] Preferably, in step (1), the molar ratio of CsBr, AgBr and BiBr3 is 2:1 to 1.6:1 to 1.6.
[0013] Preferably, in step (1), the usage ratio of CsBr to the mixed solvent is 0.02-0.15 mmol:1 mL.
[0014] Preferably, in step (1), in the mixed solvent, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 3:0.5-1.5.
[0015] Preferably, the mass ratio of CsBr to g-C3N4 is 1:0.5-5.
[0016] Preferably, in step (2), the usage ratio of g-C3N4 to N,N-dimethylformamide is 20-30 mg:1 mL.
[0017] Preferably, the g-C3N4 is prepared according to the following process:
[0018] The dicyandiamide is subjected to hydrothermal reaction and high temperature cracking.
[0019] Preferably, the conditions of the hydrothermal reaction include: temperature of 180-250° C., time of 4-10 h;
[0020] Preferably, the conditions for high temperature pyrolysis include: a temperature of 500 to 600° C. and a time of 1 to 3 hours.
[0021] Preferably, in step (3), the volume ratio of toluene to the mixed liquid is greater than 10.
[0022] Preferably, in step (3), the drying conditions include: a temperature of 100 to 150° C. and a time of 4 to 10 hours.
[0023] A second aspect of the present invention provides a composite photocatalyst prepared by the method described above.
[0024] In the technical solution provided by the present invention, Cs2AgBiBr6 (CABB) is grown in situ on g-C3N4 nanosheets using an anti-solvent method to synthesize a CABB@g-C3N4 composite photocatalyst. On the one hand, the introduction of Cs2AgBiBr6 will improve the light response ability of the composite catalyst; on the other hand, a heterogeneous structure will be formed in the interface region of Cs2AgBiBr6 and g-C3N4, thereby improving the separation efficiency of electron / hole pairs, which is beneficial to the improvement of catalytic efficiency. Therefore, the CABB@g-C3N4 composite photocatalyst prepared by the present invention has the ability to efficiently reduce CO2.
[0025] Compared with Cs2AgBiBr6 and g-C3N4, the CABB@g-C3N composite photocatalyst exhibits higher catalytic activity in CO2 reduction experiments, providing a new material for photocatalytic carbon reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A schematic diagram of the structure of the CABB@g-C3N4 composite photocatalyst provided by the present invention;
[0027] Figure 2 This is a transmission electron microscopy image of the CABB@g-C3N4 composite photocatalyst prepared in Example 1 of the present invention;
[0028] Figure 3 This is a comparison chart of the photocatalytic reduction of CO2 performance of the CABB@g-C3N composite photocatalyst prepared in Example 1 of the present invention, the g-C3N4 nanosheets prepared in Comparative Example 1, and the CABB prepared in Comparative Example 2;
[0029] Figure 4 This is a graph showing the photocatalytic reduction CO2 performance test results of the CABB@g-C3N4 composite photocatalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0031] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0032] g-C3N4 is a graphite-like semiconductor that can play a photocatalytic role only under ordinary visible light without ultraviolet light. It is a good catalyst and catalyst carrier, but its catalytic efficiency of converting CO2 into CH4 is low. Lead-free double-base perovskite Cs2AgBiBr6 nanocrystals show high stability, but the reducibility they show is not enough to reduce CO2 to CH4. Even if a small amount of CH4 is generated, the efficiency is extremely low. The present invention has found through research that designing and synthesizing heterojunction photocatalytic composite materials is an effective strategy to improve catalytic efficiency, because this can significantly improve the separation efficiency of electron / hole pairs and the carrier migration length. However, the bonding behavior between photocatalytic materials is extremely complex, which also explains the difficulty of synthesizing composite photocatalysts. The traditional hot injection method for synthesizing Cs2AgBiBr6 nanocrystals requires a high temperature of 200°C, which is a relatively high energy consumption process, and the oleylamine introduced during the synthesis process will passivate the crystal surface and reduce the catalytic activity. Therefore, there are still difficulties in growing Cs2AgBiBr6 nanocrystals on g-C3N4 nanosheets.
[0033] In view of this, the present invention provides a method for preparing a composite photocatalyst, the method comprising: using an anti-solvent method to in-situ grow Cs2AgBiBr6 on g-C3N4.
[0034] The present invention uses an anti-solvent method to in-situ grow Cs2AgBiBr6 (CABB) nanocrystals on g-C3N4 nanosheets, which reduces energy consumption compared to the traditional hot injection method, and the synthesis steps are simple, the operation is simple and easy to implement, and it has practical production potential; at the same time, the CABB@g-C3N4 composite photocatalyst forms a heterojunction structure in the interface region, which improves the electron / hole separation efficiency and increases the carrier migration length. Therefore, the CABB@g-C3N4 composite photocatalyst prepared by the present invention has the ability to efficiently reduce CO2.
[0035] The CABB@g-C3N4 composite photocatalyst prepared by the present invention has a catalytic efficiency higher than that of pure CABB and g-C3N4 in a CO2 reduction experiment, providing a new material for photocatalytic carbon reduction.
[0036] In a preferred embodiment, the method comprises the following steps:
[0037] (1) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution;
[0038] (2) mixing g-C3N4 with N,N-dimethylformamide (DMF), and then mixing with the precursor solution to obtain a mixed solution;
[0039] (3) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst;
[0040] Wherein, in step (1), the mixed solvent contains N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).
[0041] Please refer to Figure 1 In the CABB@g-C3N4 composite photocatalyst prepared by the present invention, g-C3N4 is a polymer compound with coplanar tris-s-triazine as the basic structural unit, and CABB shows a typical A2BB′X6 crystal structure, in which the Ag at the B and B′ sites + and Bi 3+ Ion and Br - Combined to form two types of regular octahedrons, these two types of octahedrons are alternately connected to form a face-centered cubic structure. The Cs with a larger ionic radius + Fill in its gaps.
[0042] In a specific implementation, step (1) includes: dissolving CsBr, AgBr and BiBr3 in a mixed solvent of DMF and DMSO.
[0043] In a preferred embodiment, in step (1), the molar ratio of CsBr, AgBr and BiBr3 is 2:1-1.6:1-1.6, specifically, for example, 2:1:1, 2:1:1.2, 2:1.1:1.1, 2:1.2:1.2, 2:1.2:1.3, 2:1.3:1.3, 2:1.4:1.2, 2:1.3:1.4, 2:1.4:1.4, 2:1.4:1.5 or 2:1.6:1.6. That is, in the precursor solution, the molar ratio of CsBr, AgBr and BiBr3 is 2:1-1.6:1-1.6.
[0044] In a preferred embodiment, in step (1), the usage ratio of CsBr to the mixed solvent is 0.02-0.15 mmol:1 mL, more preferably 0.028-0.112 mmol:1 mL.
[0045] In a preferred embodiment, in step (1), in the mixed solvent, the volume ratio of DMF to DMSO is 3:0.5-1.5, preferably 3:0.8-1.3, specifically, for example, it can be 3:0.8, 3:0.9, 3:1, 3:1.1, 3:1.2 or 3:1.3.
[0046] In a preferred embodiment, the mass ratio of CsBr to g-C3N4 is 1:0.5-5, preferably 1:1-4.
[0047] In a preferred embodiment, in step (2), the usage ratio of g-C3N4 to N,N-dimethylformamide is 20-30 mg:1 mL.
[0048] The present invention does not limit the specific source of the g-C3N4, which can be purchased or prepared by itself. In the present invention, a self-preparation method is adopted. In a preferred embodiment, the g-C3N4 is prepared according to the following process: dicyandiamide is subjected to hydrothermal reaction and high-temperature cracking. In this process, dicyandiamide is used as a raw material, which has low cost and abundant sources, and the prepared g-C3N4 nanosheets have a smooth morphology and a regular two-dimensional structure.
[0049] In a specific embodiment, the g-C3N4 is prepared according to the following process: dicyandiamide is mixed with deionized water, and then ultrasonicated for 20 to 60 minutes to obtain a dispersion, and the dispersion is transferred to a reactor for hydrothermal reaction, followed by high-temperature pyrolysis to obtain g-C3N4 nanosheets.
[0050] In a preferred embodiment, the temperature of the hydrothermal reaction is 180-250° C., preferably 200-210° C.; the time of the hydrothermal reaction is 4-10 h, preferably 6-8 h.
[0051] In a preferred embodiment, the temperature of the high temperature pyrolysis is 500-600°C, preferably 530-550°C; the time of the high temperature pyrolysis is 1-3h, preferably 2-3h.
[0052] In a specific embodiment, step (3) comprises: slowly dropping the mixed solution into stirring toluene, stirring thoroughly for 3 to 10 minutes, and then centrifuging, and drying the solid obtained by centrifugation to obtain a CABB@g-C3N4 composite photocatalyst.
[0053] In a preferred embodiment, in step (3), the volume ratio of toluene to the mixed liquid is greater than 10, preferably 10-20.
[0054] In a preferred embodiment, in step (3), the drying temperature is 100-150° C., preferably 120-130° C.; the drying time is 4-10 h, preferably 6-8 h.
[0055] In one embodiment, the method comprises the following steps: (1) subjecting dicyandiamide to hydrothermal reaction and high temperature cracking to obtain g-C3N4; (2) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution; (3) mixing the g-C3N4 with N,N-dimethylformamide, and then mixing with the precursor solution to obtain a mixed solution; (4) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst.
[0056] In another embodiment, the method comprises the following steps: (1) subjecting dicyandiamide to hydrothermal reaction and high temperature cracking to obtain g-C3N4; (2) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution; (3) mixing the g-C3N4 with N,N-dimethylformamide, and then mixing with the precursor solution to obtain a mixed solution; (4) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst; wherein the molar ratio of the amounts of CsBr, AgBr and BiBr3 is 2:1 to 1.6:1 to 1.6.
[0057] In another embodiment, the method comprises the following steps: (1) subjecting dicyandiamide to hydrothermal reaction and high temperature cracking to obtain g-C3N4; (2) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution; (3) mixing the g-C3N4 with N,N-dimethylformamide, and then mixing with the precursor solution to obtain a mixed solution; (4) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst; wherein the molar ratio of the amounts of CsBr, AgBr and BiBr3 is 2:1 to 1.6:1 to 1.6; and the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide in the mixed solvent is 3:0.5 to 1.5.
[0058] In another embodiment, the method comprises the following steps: (1) subjecting dicyandiamide to hydrothermal reaction and high temperature cracking to obtain g-C3N4; (2) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution; (3) mixing the g-C3N4 with N,N-dimethylformamide, and then mixing with the precursor solution to obtain a mixed solution; (4) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst; wherein the molar ratio of the amounts of CsBr, AgBr and BiBr3 is 2:1 to 1.6:1 to 1.6; in the mixed solvent, the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide is 3:0.5 to 1.5; and the mass ratio of the amounts of CsBr and g-C3N4 is 1:0.5 to 5.
[0059] In another embodiment, the method comprises the following steps: (1) subjecting dicyandiamide to hydrothermal reaction and high temperature cracking to obtain g-C3N4; (2) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution; (3) mixing the g-C3N4 with N,N-dimethylformamide, and then mixing with the precursor solution to obtain a mixed solution; (4) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst; wherein the molar ratio of the amounts of CsBr, AgBr and BiBr3 is 2:1 to 1.6:1 to 1.6; in the mixed solvent, the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide is 3:0.5 to 1.5; the mass ratio of the amounts of CsBr and g-C3N4 is 1:0.5 to 5; and the volume ratio of toluene to the mixed solution is greater than 10.
[0060] The present invention also provides a composite photocatalyst prepared by the method as described above.
[0061] The composite photocatalyst prepared by the present invention has the advantages of simple synthesis steps, simple and easy operation, high catalytic efficiency, etc., and has broad application prospects in the field of CO2 reduction.
[0062] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto. In the following examples, toluene is AR pure with a purity of 99.5%.
[0063] Example 1
[0064] This example is used to illustrate the composite photocatalyst and its preparation method.
[0065] (1) Weighing 1 g of dicyandiamide and dispersing it into 25 mL of deionized water, ultrasonicating it for 30 min to obtain a uniform dispersion; transferring the dispersion into a 50 mL polytetrafluoroethylene liner reactor, reacting it at 200° C. for 4 h, and after the reactor is cooled, collecting the white powder by centrifugation and drying it; finally, placing the powder in a muffle furnace and pyrolyzing it at 550° C. for 2 h to obtain g-C3N4 nanosheets;
[0066] (2) 0.056 mmol CsBr (i.e., 11.92 mg), 0.028 mmol AgBr, and 0.028 mmol BiBr3 were dissolved in 1 mL of a mixed solvent (mixed with DMF and DMSO in a volume ratio of 3:1) to obtain a CABB precursor solution, i.e., a molar ratio of CsBr:AgBr:BiBr3 of 2:1:1;
[0067] (3) 25 mg of the g-C3N4 nanosheets were added to 1 mL of DMF and ultrasonically treated for 30 min to obtain a uniformly dispersed suspension, and then mixed with the CABB precursor solution and ultrasonicated for 30 min to fully mix and obtain a mixed solution, that is, the mass ratio of the CsBr to g-C3N4 was 1:2.1;
[0068] (4) The mixed solution was slowly dropped into 25 mL of stirring toluene, stirred for 5 min, and then centrifuged. The solid obtained by centrifugation was then placed in a vacuum drying oven at 120° C. and dried for 6 h. The obtained product was the CABB@g-C3N4 composite catalyst.
[0069] Example 2
[0070] (1) Weighing 1 g of dicyandiamide and dispersing it into 25 mL of deionized water, ultrasonicating it for 30 min to obtain a uniform dispersion; transferring the dispersion into a 50 mL polytetrafluoroethylene liner reactor, reacting it at 210° C. for 3 h, and after the reactor is cooled, collecting the white powder by centrifugation and drying it; finally, placing the powder in a muffle furnace and pyrolyzing it at 570° C. for 2 h to obtain g-C3N4 nanosheets;
[0071] (2) 0.112 mmol CsBr (i.e., 23.83 mg), 0.056 mmol AgBr, and 0.056 mmol BiBr3 were dissolved in 1 mL of a mixed solvent (mixed with DMF and DMSO in a volume ratio of 3:1) to obtain a CABB precursor solution, i.e., a molar ratio of CsBr:AgBr:BiBr3 of 2:1:1;
[0072] (3) 25 mg of the g-C3N4 nanosheets were added to 1 mL of DMF and ultrasonically treated for 30 min to obtain a uniformly dispersed suspension, and then mixed with the CABB precursor solution and ultrasonicated for 30 min to fully mix and obtain a mixed solution, that is, the mass ratio of the CsBr to g-C3N4 was 1:1.05;
[0073] (4) The mixed solution was slowly dropped into 30 mL of stirring toluene, stirred for 5 min, and then centrifuged. The solid obtained by centrifugation was then placed in a vacuum drying oven at 120° C. and dried for 6 h. The obtained product was the CABB@g-C3N4 composite catalyst.
[0074] Example 3
[0075] (1) Weighing 1 g of dicyandiamide and dispersing it into 25 mL of deionized water, ultrasonicating it for 30 min to obtain a uniform dispersion; transferring the dispersion into a 50 mL polytetrafluoroethylene liner reactor, reacting it at 215° C. for 4 h, and after the reactor is cooled, collecting the white powder by centrifugation and drying it; finally, placing the powder in a muffle furnace and pyrolyzing it at 540° C. for 3 h to obtain g-C3N4 nanosheets;
[0076] (2) 0.028 mmol CsBr (i.e., 5.96 mg), 0.014 mmol AgBr, and 0.014 mmol BiBr3 were dissolved in 1 mL of a mixed solvent (mixed with DMF and DMSO in a volume ratio of 3:1) to obtain a CABB precursor solution, i.e., a molar ratio of CsBr:AgBr:BiBr3 of 2:1:1;
[0077] (3) 22 mg of the above g-C3N4 nanosheets were added to 1 mL of DMF and ultrasonically treated for 30 min to obtain a uniformly dispersed suspension, and then mixed with the above CABB precursor solution and ultrasonicated for 30 min to fully mix and obtain a mixed solution, that is, the mass ratio of the CsBr to g-C3N4 was 1:3.96;
[0078] (4) The mixed solution was slowly dropped into 30 mL of stirring toluene, stirred for 5 min, and then centrifuged. The solid obtained by centrifugation was then placed in a vacuum drying oven at 150° C. and dried for 5 h. The obtained product was the CABB@g-C3N4 composite catalyst.
[0079] Comparative Example 1
[0080] Preparation of g-C3N4 nanosheets:
[0081] The g-C3N4 nanosheets were prepared according to the method described in Example 1, specifically, comprising the following steps:
[0082] Weigh 1 g of dicyandiamide and disperse it in 25 mL of deionized water, and ultrasonicate for 30 min to obtain a uniform dispersion; transfer the dispersion to a 50 mL polytetrafluoroethylene reactor, react at 200 ° C for 4 h, and after the reactor is cooled, collect the white powder by centrifugation and dry it; finally, place the powder in a muffle furnace and pyrolyze it at 550 ° C for 2 h to obtain g-C3N4 nanosheets.
[0083] Comparative Example 2
[0084] Preparation of lead-free double-base perovskite CABB:
[0085] (1) 0.056 mmol CsBr (i.e., 23.83 mg), 0.028 mmol AgBr, and 0.028 mmol BiBr3 were dissolved in 1 mL of a mixed solvent (mixed with DMF and DMSO in a volume ratio of 3:1) to obtain a CABB precursor solution, i.e., a molar ratio of CsBr:AgBr:BiBr3 of 2:1:1;
[0086] (2) The CABB precursor solution is slowly dripped into the stirred toluene, stirred for 5 min, and then centrifuged. The solid obtained by centrifugation is then placed in a vacuum drying oven at 120° C. and dried for 6 h. The obtained product is CABB.
[0087] Test Example 1
[0088] The CABB@g-C3N4 composite photocatalyst prepared in Example 1 was characterized by transmission electron microscopy (TEM). Figure 2 As shown in (a and b).
[0089] Figure 2 The image in (a) shows that CABBs are densely loaded on g-C3N4 nanosheets, and the average size of CABBs is less than 20 nm. Figure 2 (b) is a high-resolution image of CABB loaded on g-C3N4. The measured lattice plane spacing is 0.339nm, corresponding to the (3 1 1) crystal plane of CABB. The above TEM images provide direct evidence for the successful loading of CABB on g-C3N4 nanosheets.
[0090] Test Example 2
[0091] The CABB@g-C3N composite photocatalyst prepared in Example 1, the g-C3N4 nanosheets prepared in Comparative Example 1, and the CABB prepared in Comparative Example 2 were tested for their photocatalytic reduction of CO2 performance.
[0092] Test method: Under visible light irradiation (λ>420nm, 80mW cm -2 ) was carried out in a solution of 100 mL of ethyl acetate, with 10% of the solution volume of triethylamine added as a sacrificial agent. 20 mg of the catalyst was dispersed using magnetic stirring and ultrasonic waves, and then the suspension was transferred to a quartz glass reactor with a condensed water circulation system, and Ar gas was introduced at a flow rate of 20 sccm for 10 minutes to completely replace the air, and then high-purity CO2 gas (5N) was introduced at a flow rate of 8 sccm. The light source was a 300 W xenon lamp with a 420 nm cutoff filter. The light intensity was 80 mW / cm 2 , the incident area is π*(4.5 / 2) 2 cm2 To ensure sufficient reaction, the reaction was carried out under 500 rpm / min magnetic stirring. The reaction product was analyzed by Agilent GC7890 (FID and TCD).
[0093] Test results: The catalytic efficiency of the products obtained in Example 1 and Comparative Examples 1-2 in reducing CO2 under visible light is as follows: Figure 3 and Figure 4 shown.
[0094] Depend on Figure 3 It can be seen that the generation of CO and CH4 by CABB@g-C3N4 prepared in Example 1 is significantly higher than that by g-C3N4 prepared in Comparative Example 1 and CABB prepared in Comparative Example 2. The average generation rates of CO and CH4 of CABB@g-C3N4 composite photocatalyst are 35.8 μmol·g -1 ·h -1 and 13.5 μmol·g -1 ·h -1 .
[0095] Depend on Figure 4 It can be seen that the CO and CH4 production of CABB@g-C3N4 composite photocatalyst almost shows a linear growth trend with the extension of reaction time. The cumulative production of CO and CH4 in 260 min reaches 155.3 and 57.2 μmol·g, respectively. -1 At the same time, according to the formula (TCelectron = 2TC(CO) + 8TC(CH4), where TCelectron, TC(CO) and TC(CH4) are the total electron consumption, the cumulative CO generation and the cumulative CH4 generation, respectively), the total electron consumption of CABB@g-C3N4 composite photocatalyst within 260 minutes was calculated to be 768.9 μmol·g -1 .
[0096] It should be noted that the preparation principle of Example 2-3 is similar to that of Example 1. Therefore, the composite photocatalyst prepared therefrom also has the ability to efficiently reduce CO2, and its photocatalytic reduction performance of CO2 is better than that of the g-C3N4 nanosheets prepared in Comparative Example 1 and the CABB prepared in Comparative Example 2.
[0097] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a composite photocatalyst, characterized in that: The method comprises: using an anti-solvent method to in-situ grow Cs2AgBiBr6 on g-C3N4.
2. The method according to claim 1, characterized in that The method comprises the following steps: (1) mixing CsBr, AgBr and BiBr3 with a mixed solvent to obtain a precursor solution; (2) mixing g-C3N4 with N,N-dimethylformamide, and then mixing with the precursor solution to obtain a mixed solution; (3) mixing the mixed solution with toluene, followed by centrifugation and drying to obtain a composite photocatalyst; Wherein, in step (1), the mixed solvent contains N,N-dimethylformamide and dimethyl sulfoxide.
3. The method according to claim 2, characterized in that In step (1), the molar ratio of CsBr, AgBr and BiBr3 is 2:1-1.6:1-1.6; Preferably, in step (1), the ratio of CsBr to the mixed solvent is 0.02-0.15 mmol:1 mL; Preferably, in step (1), in the mixed solvent, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 3:0.5-1.
5.
4. The method according to claim 2, characterized in that: The mass ratio of the CsBr to g-C3N4 is 1:0.5-5.
5. The method according to claim 2, characterized in that: In step (2), the usage ratio of g-C3N4 to N,N-dimethylformamide is 20-30 mg:1 mL.
6. The method according to claim 2, characterized in that The g-C3N4 is prepared according to the following process: The dicyandiamide is subjected to hydrothermal reaction and high temperature cracking.
7. The method according to claim 6, characterized in that The conditions of the hydrothermal reaction include: temperature of 180-250° C. and time of 4-10 h; Preferably, the conditions for high temperature pyrolysis include: a temperature of 500 to 600° C. and a time of 1 to 3 hours.
8. The method according to claim 2, characterized in that: In step (3), the volume ratio of toluene to the mixed liquid is greater than 10.
9. The method according to claim 2, characterized in that: In step (3), the drying conditions include: temperature of 100 to 150° C. and time of 4 to 10 hours.
10. A composite photocatalyst prepared by the method according to any one of claims 1 to 9.
